2008
DOI: 10.1002/ejoc.200701000
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anion‐Binding Studies of Thiaphlorins and Covalently Linked Thiaphlorin–Porphyrin Dyads

Abstract: A series of thiaphlorins with N 2 S 2 and N 3 S cores have been prepared in decent yields from readily available precursors. The thiaphlorins were characterized by all spectroscopic techniques and the structures of two thiaphlorins were solved by X-ray crystallography. The spectral studies indicated that the properties of thiaphlorins were quite different from those of thiaporphyrins. The methodology used for the synthesis of thiaphlorins has been extended to synthesize a series of monofunctionalized thiaphlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…Bismuth(III) tert-butoxide, 2,4-dimethoxybenzyl alcohol, and 2-(2-thienyl)iso-propyl alcohol were prepared according to literature procedures. [47][48][49] Materials characterization NMR spectra were measured by using aBruker AvanceIII 500 spectrometer (500. H} cross polarization magic-angle spinning (CP MAS) NMR spectra were recorded by using aB ruker Avance4 00 spectrometer at 100.6 MHz.…”
Section: Chemicalsmentioning
confidence: 99%
“…Bismuth(III) tert-butoxide, 2,4-dimethoxybenzyl alcohol, and 2-(2-thienyl)iso-propyl alcohol were prepared according to literature procedures. [47][48][49] Materials characterization NMR spectra were measured by using aBruker AvanceIII 500 spectrometer (500. H} cross polarization magic-angle spinning (CP MAS) NMR spectra were recorded by using aB ruker Avance4 00 spectrometer at 100.6 MHz.…”
Section: Chemicalsmentioning
confidence: 99%
“…4). 35 The thiaphlorin building blocks 77-85 were used to synthesize novel porphyrin-thiaphlorin dyads 86-91 (Chart 3) by coupling of appropriate thiaphlorin building blocks containing iodophenyl functional group with porphyrin building blocks with meso-ethynyl phenyl functional group under copper free mild Pd(0) coupling conditions. 29 The porphyrin-phlorin dyads such as ZnN 4 -N 2 S 2 dyad 88 and N 3 S-N 2 S 2 dyad 91 were demonstrated as a fluorescence anion sensors.…”
Section: Mono-functionalized Heteroporphyrin Building Blocksmentioning
confidence: 99%
“…In continuation of our efforts in synthesizing core-modified calixphyrins to study their potential use for anion and metal-binding, in this paper we report the synthesis of expanded dithiacalixphyrins 3 containing two thiophene rings and two pyrrole rings bridged via three sp 2 and two sp 3 meso-carbons (Chart 1). These expanded thiacalixphyrins 3 are immediate higher analogues of thiacalixphyrins 19,20 and contain one extra meso carbon compared to the reported thiacalixphyrins 1 and 2. The expanded thiacalixphyrins 3 containing two meso-sp 3 carbons along with three meso-sp 2 carbons and one extra meso-carbon compared to thiacalixphyrin induce sufficient flexibility in the macrocycle ring and the crystal structure revealed that the macrocycle is highly distorted.…”
Section: Introductionmentioning
confidence: 88%